Marx, Materialism and the Brain: Determination in the Last Instance? - Joss Hands (tripleC: Communication, Capitalism & Critique)
It is well acknowledged that there is not one but many Marxes, and one area where this has been most evident is in the question of technological and economic determinism. This article traces some key moments in this debate and attempts to locate their most recent iteration in disagreements over the place of the human brain in both historical agency and value creation in so called ‘cognitive’ or ‘post-Fordist’ capitalism. Of significant interest in the current configuration – or rather composition – of capital is the place of the digitisation of the labour process and its relation to, and integration with, human cognition and volition. Arguments over the attention economy and the power of post-Fordist capitalism to distract and direct is a significant variation of the question of ideology and the latest variation of the base/superstructure debate. This article will unpack the aforesaid issues to offer an articulated perspective in order to make the argument that taking a balanced view of determination will allow us to acknowledge that – drawing on the argument of determination in the last instance – we can hold both of these ‘Marxes’ to be simultaneously valid. Here, a revisiting of Marx’s concept of General Intellect will be undertaken, wherein the productive capacity of living labour is employed in both active agency and the capture of value, in which the plasticity of the living brain becomes the pivot point for both exploitation by, and resistance to, capital.